2012
DOI: 10.5539/ies.v5n2p24
|View full text |Cite
|
Sign up to set email alerts
|

Reading Preferences and Strategies Employed by Primary School Students: Gender, Socio-Cognitive and Citizenship Issues

Abstract: The purpose of the present study was to identify the correlation between gender and reading preferences and reading strategies employed by 5th and 6th Grade students of primary school in Greece. The main objectives of the present study were (1) to identify possible differences between male and female students in employing cognitive and metacognitive strategies, (2) to record the difficulties encountered by males and females when reading and (3) to highlight possible differences between male and female students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 31 publications
(21 reference statements)
2
10
1
4
Order By: Relevance
“…However, the findings of the current study partly support those of Phakiti (2003) who reported no significant difference between males and females in cognitive strategy use. This part of results is also opposite to the findings of Griva, Alevriadou, and Semoglou (2012) who reported that females used cognitive strategies more frequently and efficiently than males. The findings also support those of Poole's (2005) who found no significant difference between males and females in their total strategy use.…”
Section: Discussioncontrasting
confidence: 84%
“…However, the findings of the current study partly support those of Phakiti (2003) who reported no significant difference between males and females in cognitive strategy use. This part of results is also opposite to the findings of Griva, Alevriadou, and Semoglou (2012) who reported that females used cognitive strategies more frequently and efficiently than males. The findings also support those of Poole's (2005) who found no significant difference between males and females in their total strategy use.…”
Section: Discussioncontrasting
confidence: 84%
“…These results supported girls' better achievements in reading comprehension tests evidencing that were also aware of employing effective reading strategies. Girls' more extensive and flexible use of cognitive and metacognitive strategies is also supported by the results of other studies (Green & Oxford 1995;Griva et al 2009;Griva et al 2012). Significant differences between EFL individual reading strategies use were displayed in up to 7 out of 30 in total, mostly being problem-solving and support strategies, such as re-reading text or paying closer attention when text becomes difficult, guessing meaning of unknown words, underlining information, trying not to lose concentration and questioning themselves about the text.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 69%
“…Specifically, besides reporting higher levels of 'global strategies' use, effective L2/FL learners also showed flexibility in using various strategy categories and greater awareness of processing strategies to monitor their reading (O'Malley & Chamot 1990;Nyikos & Oxford 1993). Contrastively, less successful readers use local strategies (Huang, Chern & Lin 2009), are not aware of identifying reading problems (Shen 2003), and do not know how to 'orchestrate' a variety of strategies for effective comprehension purposes (Griva, Alevriadou & Geladari 2009;Griva, Alevriadou & Semoglou 2012). Moreover, gender differences in the frequency and flexibility of strategy use have been indicated in a number of studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They explained that one main reason for the relatively negative attitude of boys towards reading was the fact that boys tended to view reading as being an uncool and effeminate activity. Griva, Alevriadou and Semoglou (2012) identified the correlation between gender and reading preferences and attitudes of 6th Grade students of primary school in Greece. Byro (2000) determined the relationship between reading attitude and gender to compare reading attitudes between boys and girls regarding both academic and recreational reading.…”
Section: Gender and Attitudes Towards Recreational Reading And Academmentioning
confidence: 99%